PERAN KONFLIK KOGNITIF DAN AFEKTIF PADA IMPLEMENTASI ACTIVITY BASED COST MANAJEMENT PADA PERUSAHAAN MANUFAKTUR DI JAWA TENGAH - Supartini, Supartini (Universitas Muhammadiyah Magelang, 2007)
Review the key factors on the success of the implementation of ABCM associated with the support of top management, clearly goals, and training. Conflicts tend to appear during the implementation of ABCM. Conflicts that have a beneficial impact is considered a cognitive conflict, while the conflict is often seen as disfungsional affective conflict. Managers from 72 manufacturing companies in Central Java as the only respondent to prove the purpose of clarity associated with positive cognitive conflict. Clarity is also the purpose of dealing with the positive use of ABCM for product planning and financial management. Both cognitive conflict and affective conflict purpose not related to financial management for ABCM. Cognitive conflict-related purposes only ABCM for product planning. This shows that the conflict is both cognitive conflict and affective conflict is something that should be avoided, if there is a conflict had not grown and not directly.